DEFICIENCY OF INTERLEUKIN-1 RECEPTOR ANTAGONIST RESPONSIVE TO ANAKINRA - SCHNELLBACHER, CHARLOTTE (2012)
We describe a 3-month-old infant who presented to our institution with interleukin (IL)-1 receptor antagonist deficiency (DIRA), which consists of neutrophilic pustular dermatosis, periostitis, aseptic multifocal osteomyelitis, and persistently high acutephase reactants. Skin findings promptly improved upon initiation of treatment with anakinra (recombinant human IL-1 receptor antagonist), and the bony lesions and systemic inflammation resolved with continued therapy.